Integrated physical–chemical mechanisms drive carbon stabilization under conservation tillage in Karst agroecosystems - Xu, Guang; Mo, Qishun; Li, Zhou; Qin, Wangfei; Dong, Rui; Zhao, Xuechun; Chen, Chao; Gunina, Anna; Shurpali, Narasinha; Thentu, Tulasi Lakshmi; Nie, Gang; Li, Yuan (Elsevier, 2025)
Conservation tillage practices improve soil fertility and enhance soil organic carbon (SOC) sequestration in fragile Karst agroecosystems. In a three-year field experiment in Southwest China aimed to compare conventional tillage (CT), conventional tillage-mulching (CTM), no-tillage without mulching (NT), and no-tillage-mulching (NTM) and evaluate their effects on SOC accumulation in aggregation, changes in SOC composition and actives of C-related enzymes at depths of 0 – 5, 5 – 10, and 10 – 20  cm. Large macroaggregates (> 2 mm) dominated (54 – 64 %), and NTM increased the proportion of > 2 mm aggregates in the 0 – 5  cm. All conservation tillage practices enhanced macroaggregate stability, with NTM showing the greatest improvements in mean weight diameter and SOC content across aggregate size classes. FTIR indicated that NTM increased the intensity of carboxyl-C in macroaggregates, suggesting enhanced chemical stabilization. Soil oxidases (polyphenol oxidase, peroxidase) and hydrolases (β-1,4-glucosidase) generally increased under conservation tillage, although responses of other enzymes (e.g., cellobiohydrolase, β-xylosidase) varied by depth and aggregate size. Structural equation modeling revealed that no-tillage promoted enzyme activities (path coefficient = 0.77), while mulching improved soil aggregation (0.60) and enzyme activities (0.32), which all increased SOC content. Thus, no-tillage combined with mulching is the most effective strategy for improving aggregate stability, SOC content, and enzymatic activities in Karst agricultural systems, offering a practical approach for sustainable land management.
Keywords: aggregate stability; carbon fractions; conservation tillage; FTIR spectroscopy